Pyrolysis, kinetics, and structural analyses of agricultural residues in Egypt: For future assessment of their energy potential - Mohamed Nour (Cleaner Engineering and Technology, 2021)
Agricultural residues receive significant attention worldwide as a sustainable and green energy source. The accurate assessment of agricultural residues’ energy potential depends on physicochemical properties that change with location and climate. Several studies provide an imprecise estimation of agricultural residues’ energy potential in Egypt based on characteristics in literature from other sites. This study investigates the physicochemical properties, pyrolysis, and kinetics of seven types of agricultural residues, namely corn stalks, switchgrass, okra stems along with ficus, camphor, desert olive, and blueberry tree woodchips sampled from several locations in Egypt. The thermogravimetric, differential thermal, proximate, ultimate, lignocellulosic constituents, kinetics, crystallinity, and microstructure analyses are used to characterize the biomass. Kinetic parameters were determined by applying Coats-Redfern and Direct-Arrhenius approaches. The results revealed that woody residues have higher volatile matters, energy contents, hemicellulose, and lignin with lower ash, moisture, and cellulose than herbaceous residues. The activation energies of woody residues are lower than that of switchgrass and okra stems but higher than Cornstalks. The tested residues are bulk with nonuniform crystal structures, and their usages require further processing. The woody residues have promising properties. This study facilitates the accurate assessment of the agricultural residues’ energy potential in Egypt.